School feeding reduces anemia prevalence in adolescent girls and other vulnerable household members in a cluster randomized controlled trial in Uganda - Adelman, Sarah W.; Gilligan, Daniel O.; Konde-Lule, Joseph; Alderman, Harold (Elsevier, 2019)
Food for education (FFE) programs that include school meals are widely used to improve school participation and performance, but evidence on nutritional benefits is limited. This study tested whether food fortified with multiple micronutrients provided in FFE programs reduced anemia prevalence of primary-school-age adolescent girls, adult women, and preschool children.